2014
DOI: 10.2527/jas.2014-7903
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in histomorphology and gene expression in goat testes during postnatal development1,2

Abstract: Testicular cell proliferation and differentiation is critical for development of normal testicular function and male reproductive maturity. The objective of the current study was to evaluate histoarchitecture and expression of genes marking specific cells and important functions as well as testosterone production of the developing goat testes. Testes were harvested from Alpine bucks at 0, 2, 4, 6, and 8 mo of age (n = 5/age group). Paired testes weight increased from 2 to 4 (P < 0.001) and 4 to 6 mo (P < 0.01)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…Other studies have reported a decline in FSHR levels in rat and mice testes as they age (Ketelslegers et al 1978). However, this result may be affected by an increase in germ cell population, causing an overall dilution of FSHR (Faucette et al 2014). Given the absence of an effect of plane of nutrition on systemic FSH concentration or indeed FSHβ transcript abundance in the anterior pituitary, in our study, it is not entirely surprising that there was no effect on testicular FSHR expression.…”
Section: Figurecontrasting
confidence: 41%
“…Other studies have reported a decline in FSHR levels in rat and mice testes as they age (Ketelslegers et al 1978). However, this result may be affected by an increase in germ cell population, causing an overall dilution of FSHR (Faucette et al 2014). Given the absence of an effect of plane of nutrition on systemic FSH concentration or indeed FSHβ transcript abundance in the anterior pituitary, in our study, it is not entirely surprising that there was no effect on testicular FSHR expression.…”
Section: Figurecontrasting
confidence: 41%
“…Among them, HMGB1, as a paracrine host defense factor in the testis, was translocated from testicular cells and blocking its action by ethyl pyruvate regulated inflammatory reactions in testes and spermatogenic damage ( 68 , 69 ). Testis-specific HSPA8 gene was confirmed to decrease with the development of goat testis, which may be due to dilution by the maturing germ cell population ( 70 ). Lower concentrations of HSPA8 were associated with subfertility in men ( 71 ).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, we observed an immune signal associated to STRA8 in the spotted areas across the germinal epithelium in seminiferous tubules, showing a higher intensity in the basal compartment. STRA8 expression levels have been reported to peak at 6 months of age in goat testis and has been associated to the onset of meiosis with the highest intensity levels in preleptotene/early leptotene spermatocytes ( 29 , 30 ). Levels of the BOULE expression in goat has been reported to increase in the adult compared to the immature testis, which may be associated to an increasing number of BOULE positive spermatogonial cells at the adult stage ( 31 ).…”
Section: Discussionmentioning
confidence: 99%